1991
DOI: 10.1111/j.1365-2222.1991.tb00804.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate hypersensitivity to Parthenium hysterophorus. II. Clinical studies on the prevalence of parthenium rhinitis

Abstract: The airborne pollen of the South American weed, Parthenium hysterophorus (American feverfew), accidentally introduced into India was found to be responsible for severe allergic rhinitis. A random clinical survey conducted on 2035 residents of Bangalore city with the aid of questionnaires and skin tests revealed that 7.1% of the study population was suffering from allergic rhinitis due to exposure to Parthenium pollen. Skin-prick tests performed on 1294 clinic patients suffering from nasobronchial allergy durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…Jayachandra (1971) stated that the parthenium can be a serious problem in grasslands and can reduce the pasture carrying capacity by up to 90%. It is also known to cause human health problems like asthma, bronchitis, dermatitis, and hay fever (Kololgi et al, 1997;Srirama Rao et al, 1991). Evans (1997) and Towers and Subba Rao (1992) also reported that close contact with P. hysterophorus could cause allergic contact dermatitis while inhalation of pollen can cause allergic rhinitis, which can develop into bronchitis or asthma in susceptible humans.…”
Section: Introductionmentioning
confidence: 99%
“…Jayachandra (1971) stated that the parthenium can be a serious problem in grasslands and can reduce the pasture carrying capacity by up to 90%. It is also known to cause human health problems like asthma, bronchitis, dermatitis, and hay fever (Kololgi et al, 1997;Srirama Rao et al, 1991). Evans (1997) and Towers and Subba Rao (1992) also reported that close contact with P. hysterophorus could cause allergic contact dermatitis while inhalation of pollen can cause allergic rhinitis, which can develop into bronchitis or asthma in susceptible humans.…”
Section: Introductionmentioning
confidence: 99%
“…The high degree of allergenic crossreactivity, if not identity, established by RAST inhibition and lymphocyte proliferation experiments seems to sug gest that the native proteins of Parthenium and ragweed pollens with different physicochemical properties bear cross-reactive IgE epitopes. The clinical and immunolog ical studies carried out in India established that {he Parthe nium weed, presumed to have been accidentally intro duced into India about 3 decades ago as a contaminant with imported wheat grains, has spread all over the coun try and is responsible for the increasing incidence of al lergic rhinitis (up to 7% of the population in regions heav ily infested with the weed [6]). It is also found to be respon sible for the high incidence of rhinitis in the Brisbane region of Australia where P hysterophorus has spread in recent years [Stewart J.A., personal commun.].…”
Section: Discussionmentioning
confidence: 99%
“…Pollen of P. hysterophorus was collected and processed as de scribed earlier [6], Defatted Parthenium pollen was extracted with PBS (pH 7.4) for 20 h at 4°C (1:10 w/v). The extract was then filtered, centrifuged at 20,000g for 20 min and diluted with equal volumes of glycerol after passing through a sterile Miliporc filter (0.45 urn).…”
Section: Preparation O F Allergen Extracts For Skin Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Contact with Parthenium plant parts, in all stages of its life cycle, causes dermatitis in man. Pollens cause air borne contact dermatitis and when inhaled cause allergic rhinitis [27] which can lead to serious respiratory problems such as asthma and bronchitis. The harmful effects are induced by secondary metabolites, particularly parthenin toxin, present in different parts of the plant [28].…”
Section: Detrimental Effectsmentioning
confidence: 99%